Physical activity participation, flourishing and academic engagement in adolescents with obesity. - McCoy, Stephanie; Rupp, Kristie (Pediatric Obesity, 2021)
Background: Adolescents with obesity are less likely to flourish and be academically engaged in comparison to their healthy weight peers. However, it is unknown how participation in physical activity influences flourishing and academic engagement in adolescents with obesity. The current study examined engagement in varying levels of physical activity and the likelihood of flourishing and academic engagement in adolescents with obesity. Methods: Analyses included 26 764 adolescents, ages 10–17 years, from the parent-reported, combined 2016–2017 National Survey of Children's Health. Participants were grouped by physical activity levels (none, low, moderate, daily). Outcome variables included flourishing (finishing tasks, staying calm when faced with a challenge and showing interest in new things) and academic engagement (completing all required homework and caring about doing well in school). Logistic regression models, adjusted for age, sex, race, household income, highest level of education in the household, behavioural conduct problems and depression assessed the likelihood of each outcome comparing physical activity levels among adolescents with obesity. Results: Adolescents with obesity who participated in any amount of physical activity (low, moderate and daily) or sports had significantly greater likelihood of flourishing and academic engagement compared those that did not engage in any physical activity (p's ¡ 0.05). Conclusions: Participation in even low amounts of physical activity or participation in sports increases the likelihood of flourishing and academic engagement in adolescents with obesity, which expands on previous findings that adolescents with obesity are less likely to flourish and be academically engaged in comparison to their healthy weight peers. © 2021 World Obesity Federation
5 citations (Crossref) [2023-10-31] Place: (C) 2021 International Association for the Study of Obesity
Keywords: Adolescent; Child; Exercise; Health Status; Humans; Pediatric Obesity; Schools; adolescence; adolescent; child; childhood obesity; dept.hms; exercise; flourishing; health status; human; obesity; peer-reviewed; physical activity; school

Physical Activity And Bullying In Adolescents With Overweight And Obesity - McCoy, Stephanie M.; Rupp, Kristie (Medicine and Science in Sports and Exercise, 2020)
WOS:000590026301543
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Perception Of Moderate Intensity Physical Activity By Onset Of Obesity: A Randomized Crossover Trial: 2347 Board# 266 May 28 2: 00 PM-3: 30 PM - Rupp, Kristie; Friel, Ciaran P. (Medicine and Science in Sports and Exercise, 2020)
0 citations (Crossref) [2023-10-31] WOS:000590026302390
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Changes in health behaviors associated with weight gain by weight classification during the COVID-19 pandemic. - Rupp, Kristie; Friel, Ciarán P (American journal of health promotion : AJHP, 2021)
Purpose: To determine whether perceived changes (i.e. perception of engagement during the pandemic relative to pre-pandemic) in specific health behaviors differ by weight status (i.e. healthy weight, overweight, obese). Design: Cross-sectional. Recruitment took place between June-August 2020, via social media posts and Qualtrics online panels. Setting: Participants completed the survey online through the Qualtrics platform. Sample: Analyses included N = 502 participants (≥18 years); 45.2% healthy weight (n = 227), 28.5% overweight (n = 143), and 26.3% obese (n = 132). Measures: Study-specific survey items included questions about demographics and perceived changes in health behaviors. Analysis: Logistic regression models, adjusted for age, race, ethnicity, gender, education, and COVID-19 diagnosis, assessed the odds of perceiving changes in health behaviors considered a risk for weight gain. Results: Participants with obesity, but not overweight, were significantly more likely to report deleterious changes to health behaviors compared to healthy weight peers, including: (1) decreased fruit/vegetable consumption [adjusted odds ratio (AOR) = 1.92; 95% confidence interval (CI): (1.13, 3.26)]; (2) increased processed food consumption [AOR = 1.85; 95%CI: (1.15, 3.00)]; (3) increased caloric intake [AOR = 1.66; 95% CI: (1.06, 2.61)]; (4) decreased physical activity [AOR = 2.07; 95%CI: (1.31, 3.28)]; and (5) deterioration in sleep quality [AOR = 2.07; 95%CI: (1.32, 3.25)]. Conclusion: Our findings suggest that adults with obesity may be at greater risk for unhealthy behaviors during a period of prolonged social distancing, potentially exacerbating the obesity epidemic. © The Author(s) 2021.
4 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34098761/ ; https://europepmc.org/article/MED/34098761 ; http://journals.sagepub.com/doi/10.1177/08901171211022958 ; https://www.ncbi.nlm.nih.gov/pubmed/34098761 ;
Keywords: COVID-19; COVID-19 Testing; Cross-Sectional Studies; Health Behavior; Humans; Pandemics; SARS-CoV-2; Sleep Quality; Weight Gain; body weight gain; cross-sectional study; dept.hms; health behavior; human; pandemic; peer-reviewed; sleep quality

Physical Activity, Sports Participation, and Psychosocial Health in Adolescents With Hearing Loss - DeLuca, Zara Waldman; Rupp, Kristie (Journal of Adolescent Health, 2022)
Purpose This study examined the association between hearing status (i.e., adolescents with and without hearing loss) and physical activity and sports participation. Secondarily, we explored the association between physical activity and sports participation and psychosocial outcomes among adolescents with hearing loss. Methods Analyses included 29,034 adolescents (52.1% male, 13.8 ± 2.3 (M ± SD) years) from the combined 2018–2019 National Survey of Children's Health. Adolescents were grouped by hearing status. Adjusted logistic regression models assessed physical activity level (i.e., 0, 1–3, 4–6, and 7 days/week) and sports participation (i.e., participation in sports within the past 12 months) by hearing status. Secondary analyses examined associations between physical activity and sports participation with psychosocial outcomes among adolescents with hearing loss adjusting for relevant confounders. Results Relative to their hearing peers, adolescents with hearing loss (n = 359) were 40% [adjusted odds ratio (AOR), 0.60; 95% confidence interval (CI), 0.44, 0.81], 43% [AOR, 0.57; 95% CI, 0.41, 0.80], and 33% [AOR, 0.67; 95% CI, 0.47, 0.95] less likely to engage in 1–3 days/week of physical activity, 4–6 days/week of physical activity, and meet physical activity guidelines, respectively. Further, adolescents with hearing loss were 31% [AOR, 0.69; 95% CI, 0.55, 0.85] less likely to participate in sports. Sports participation, but not physical activity, was associated with a significant reduction in the likelihood of experiencing adverse psychosocial outcomes among adolescents with hearing loss (p's < .05). Discussion Sports participation, but not physical activity, was associated with attenuated likelihood of experiencing adverse psychosocial outcomes in adolescents with hearing loss, suggesting unique characteristics of sports participation confer protection of psychosocial health. Increasing access to and reducing barriers to engagement in sports should be prioritized to improve psychosocial health in adolescents with hearing loss.
4 citations (Crossref) [2023-10-31]
Keywords: Hearing loss; Physical activity; Psychosocial health; Sports participation; dept.cmd; dept.hms; peer-reviewed

Understanding health behaviors, weight perceptions, and body appreciation of young adult women engaged in the body positivity movement - Rupp, Kristie; McCoy, Stephanie M. (Women's Health Issues, 2023)
Background The body positivity movement on social media is thought to foster body appreciation, but pervasive societal concern persists about the body positivity movement and the body image, health behaviors, and “normalization of obesity” of young adult women. Purpose This study explored the relationship between engagement in the body positivity movement on social media and weight status, body appreciation, body dissatisfaction, and the health behaviors of intuitive eating and physical activity in young adult women (18–35 years). Methods Participants (N = 521; ∼64% engaged in body positivity content on social media) were recruited using Qualtrics online panels for this cross-sectional survey during February 2021. Outcomes included weight status, weight consideration, weight perception, body appreciation, body dissatisfaction, physical activity, and intuitive eating. Logistic and linear regression models adjusted for age, race, ethnicity, education level, and household income were used to assess the association between engagement in the body positivity movement and specified outcomes. Results Engagement in body positivity content was associated with greater body dissatisfaction (β = 2.33, t(519) = 2.90 p = .017), body appreciation (β = 0.26, t(519) = 2.90 p = .004), and greater likelihood of reporting high amounts of physical activity (odds ratio = 2.28; p < .05) relative to nonengaged peers; these associations remained significant after further adjustment for weight status. Body positivity was not associated with weight status, weight perception, or intuitive eating. Conclusions Engagement in the body positivity movement is associated with higher body dissatisfaction and body appreciation in young adult women, which suggests they may be drawn to and engage in the body positivity movement as a protective or coping mechanism for body dissatisfaction.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

Prevalence of physical activity, sleep, and screen-time in youth before and during the covid-19 pandemic: 1735 - Rupp, Kristie; Friel, Ciaran P. (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Adolescent Concern for Body Weight and Engagement in Unhealthy Weight Control Behaviors - McCoy, Stephanie; Bryan, Jessica; Rupp, Kristie (American Journal of Health Promotion, 2025)
Keywords: Binge eating; Body mass index; Body weight; Clinical psychology; Demography; Disordered eating; Eating disorders; Environmental health; Gerontology; Internal medicine; Logistic regression; Medicine; Obesity; Odds; Odds ratio; Pill; dept.hms; eating behaviors; obesity; psychosocial health

Similar Relative Energy Deficiency In Sport (REDs) Variables In Men And Women NCAA Distance Runners - Bryan, J.; Rupp, Kristie; Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: Basal metabolic rate; Bone mineral; Doubly labeled water; Dual energy; Energy expenditure; Energy metabolism; Fat free mass; Fat mass; Physical activity; dept.hms

Comparison Of Measures Of Arterial Stiffness Between Women With And Without Polycystic Ovarian Syndrome - Lecher, Madison; Rupp, Kristie; Latchman, Peter (Medicine & Science in Sports & Exercise, 2025)
Keywords: Arterial stiffness; Blood pressure; Body mass index; Etiology; Polycystic ovary; Pulse wave velocity; dept.hms

Healthy Futures for Young Women With Obesity: A Mixed Methods Study - Rupp, Kristie; Bryan, JohnM.; Abel-Berei, Catherine (American Journal of Health Promotion, 2025)
Keywords: Focus group; Health promotion; Intervention (counseling); Mental health; Obesity; Perception; Physical activity; Psychological intervention; Psychosocial; dept.hms; health behavior; weight bias; weight stigma; women’s health

Differences in health behaviors related to overweight/obesity by race/ethnicity in a diverse urban commuter college - Rupp, Kristie; Schnoll, Roseanne; Zigmont, Victoria A. (Journal of American College Health, 2020)
Objective: To examine health behaviors associated with overweight/obesity by race/ethnicity at a diverse urban college. Participants: 270 undergraduates (77.0% female; 26.7% non-Hispanic white) and median body mass index (BMI) of 23.1 kg/m2. Methods: A questionnaire about health-related behaviors as part of the “Get Fruved” project was used to measure health behaviors (sugar sweetened beverage (SSB), fruit and vegetable consumption, physical activity, stress, and sleep) by race/ethnicity. Multivariable logistic regression was used to assess the adjusted odds of engaging in positive health-related behaviors. Results: Non-Hispanic black and Hispanic students were 64% and 59% less likely to consume lower amounts of SSB. Hispanic students were 83% and 81% less likely to meet vegetable and fruit recommendations. Non-Hispanic black and other (including biracial) had reduced odds of meeting vegetable recommendations (AOR = 0.18 and 0.28). Conclusions: Disparities in SSB, fruit, and vegetable consumption represent potential intervention targets to improve health behaviors among racial/ethnic minorities. © 2020 Taylor & Francis Group, LLC.
0 citations (Crossref) [2023-10-31] WOS:000569184800001
Keywords: College; dept.hms; dept.pch; health behavior; peer-reviewed; race/ethnicity

Perception of moderate-intensity physical activity by onset of obesity: A randomized crossover trial - Rupp, Kristie; Stewart, Andrea L.; Friel, Ciarán P. (Clinical Obesity, 2022)
Moderate-intensity physical activity is recommended for inactive adults with overweight/obesity (OW/OB). The objective of this study is to determine if differences exist in the selection of moderate intensity between inactive adults with juvenile-onset (JO) and adult-onset (AO) OW/OB. Participants (JO = 18, AO = 20) were stratified by onset and completed two separate 20-minute moderate-intensity exercise sessions on a treadmill and cycle ergometer (randomized order). Multiple linear regression was used to determine whether exercise intensity (average METS, % age-predicted HRmax), self-reported pleasure or exertion differed by onset, controlling for age and gender. On the treadmill, JO and AO participants selected an average intensity of (mean [SD]) 3.5 (0.9) and 3.7 (0.9) METS, and 64.0 (7.7) and 64.9 (7.5) % of age-predicted HRmax, respectively. On the cycle, JO and AO participants selected an average intensity of 3.3 (0.9) and 3.3 (1.0) METS, and 65.2 (8.8) and 60.7 (7.2) % of age-predicted HRmax. After adjustment, participant intensity selection did not significantly differ by obesity onset when walking or cycling. There were no significant differences in pleasure or perceived exertion by onset, however, perception of exertion was on the high-end of moderate for both the cycle (13.0, 12.5) and treadmill (12.0, 12.1), in JO and AO participants, respectively. Perception of moderate intensity did not differ by obesity onset. Self-selected intensity was at the low end of moderate for walking and cycling.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/cob.12492
Keywords: dept.hms; exercise enjoyment; overweight; peer-reviewed; perceived exertion; self-selected intensity; weight loss